2023
DOI: 10.29173/cjfy29902
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Students' Self-Efficacy in Mathematics during the Covid-19 Pandemic

Abstract: Self-efficacy in learning mathematics helps the student to overcome difficulties and challenges in problem-solving during unprecedented times. This article aims to measure the level of students' self-efficacy and its determinants during the COVID-19 pandemic in learning mathematics online. The study considered primary data from 233 students selected in a non-random approach at Visayas State University, Baybay City, Leyte, Philippines through the aid of an online survey. The data were analyzed using some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…This goes to infer that as students use the coping mechanism as they do their required tasks in online learning, they are more likely motivated to finish their work since the coping behavior of students reduces unpleasant emotions. In fact, studies have shown that coping behavior and self-efficacy must take place in students' aspects as they face the challenges in online learning to accomplish good academic achievement (Baloran, 2020;Budimir et al, 2021;Casinillo, 2023). Moreover, students' efficacy level is positively associated (rs=0.30, p-value<0.001) with their happiness in learning mathematics online at a 1% level of significance and vice versa (Table 4).…”
Section: Correlation Analysismentioning
confidence: 97%
See 4 more Smart Citations
“…This goes to infer that as students use the coping mechanism as they do their required tasks in online learning, they are more likely motivated to finish their work since the coping behavior of students reduces unpleasant emotions. In fact, studies have shown that coping behavior and self-efficacy must take place in students' aspects as they face the challenges in online learning to accomplish good academic achievement (Baloran, 2020;Budimir et al, 2021;Casinillo, 2023). Moreover, students' efficacy level is positively associated (rs=0.30, p-value<0.001) with their happiness in learning mathematics online at a 1% level of significance and vice versa (Table 4).…”
Section: Correlation Analysismentioning
confidence: 97%
“…On the other hand, self-efficacy is also part of the picture, it is the student's capacity to do things necessary to accomplish goals. In the study of Casinillo (2023), it is mentioned that self-efficacy helps students overcome the challenges during the pandemic in learning mathematics. Nurhikmah et al (2021) stated that a high level of students' self-efficacy results to lower anxiety and increases the students' well-being in doing the required task in the learning environment.…”
Section: The Framework Of the Studymentioning
confidence: 99%
See 3 more Smart Citations